Vocational education in the Philippines in Spanish times - Liesch, James R. 1928- (University of the Philippines], 1952)
This is an investigation of the course offerings of the various Spanish vocational schools in the Philippines. The point of view of this investigation is to carry a modern frame of reference to the past.